Kangaroo Rats. Observationson the Kansas species of perodipus - Popenoe, Charles Holcomb (My University, 1905)
Introduction: During the fall of 1904 it became my task to travel to the town of Kinsley, Edwards Co. Kansas, in order to investigate the depredations of the kangaroo rats (Perodipus richardsoni) in the sand hills near the place. In the investigations which followed, a number of interesting facts were secured, which, added to some previous knowledge of the animal, gained largely through a trip or two in the western part of the state, in the interests of the college entomological museum, and to much information on the subject by Prof. D. E. Lantz, then Field agent for the Experiment Station of the Kansas State Agricultural College, gave me an impulse toward the following subject. The kangaroo rats are members of the sixth family of the Rodentia, the Heteromyidae. This family is most nearly related to the Geomyidae, or pocket gophers, on the one hand, and to the Zapodidae, by jumping mice, on the other. They are characterized outwardly by the possession of fur lined, outwardly opening, cheek pouches extending back to the shoulders, and by long hind legs and feet, adapted for jumping. The characteristic features of the skull and dentition are rootless molars, narrow incisors, mastoids enormously developed and appearing on top of the skull, tympanic bones greatly inflated and possessing a nontubular metal orifice. The Heteromyidae are divided into two subfamilies, the Dipodomyinae and the Heteromyinae. The Heteromyinae includes the pocket mice of the genera. Perognathus and Heteromys, having shorter hind legs, feet with naked soles, and less fully developed tympanic bones. The mice of this group or the pocket mice are less developed for jumping, as the hind legs are not so strong, the tails are shorter and the bodies heavier than in the next group.
Citation: Popenoe, Charles Holcomb. Kangaroo Rats. Observationson the Kansas species of perodipus. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Classification of Kangaroo Rats; Habits of Kangaroo Rats; Economic Importance of Kangaroo Rats; Theses